Reviving horizontal area expansion of sunflower (Helianthus annuus L.) in rice fallow ecosystems - a relook: REVIVING HORIZONTAL AREA EXPANSION OF SUNFLOWER IN RICE FALLOW ECOSYSTEMS - A RELOOK - KULASEKARAN RAMESH; ANITA MAHAPATRA; AVIJIT ROY; SURYANARAYANA BHASKAR (Journal of Oilseeds Research, 2021)
Rice is cultivated during kharif season in Southeast Asia, but a large chunk remains uncultivated or left fallow in the subsequent season due to several reasons, the major being the water scarcity. Sunflower is cultivated in these rice fallowsin the states of Karnataka, Andhra Pradesh, Telangana, Odisha, and West Bengal and to a limited extent in other states. This is an opportunity for horizontal expansion ofsunflower area to increase the edible oil production in the country. The initial spurt in area since 1970-71 has experienced a sharp decline in spite of sunflower being one ofthe most preferred edible oils in the rural, urban and peri-urban households. Unlike the popular utera method for pulses, sunflower cultivation needs special attention. Concerted and focused research efforts are needed for fine-tuning the production technology of sunflower under rice fallow. The recent success stories of co-culturing honey bee with sunflower as a community initiative in Nizamabad district of Telangana state need to be extended to other sunflower growing regions of the country. This review critically appraises the rice fallow environments in general, determinants of sunflower production in this fragile eco-system and efforts needed for successful area-cum-production growth of sunflower crop in the country.